Post-heparin LPL activity measurement using VLDL as a substrate: a new robust method for routine assessment of plasma triglyceride lipolysis defects. - Mathilde Di Filippo; Christophe Marçais; Sybil Charrière; Oriane Marmontel; Martine Broyer; Mireille Delay; Micheline Merlin; Axel Nollace; René Valéro; Michel Lagarde; Valérie Pruneta-Deloche; Philippe Moulin; et al. (PLoS ONE, 2014)
Determination of lipoprotein lipase (LPL) activity is important for hyperchylomicronemia diagnosis, but remains both unreliable and cumbersome with current methods. Consequently by using human VLDL as substrate we developed a new LPL assay which does not require sonication, radioactive or fluorescent particles.Post-heparin plasma was added to the VLDL substrate prepared by ultracentrifugation of heat inactivated normolipidemic human serums, diluted in buffer, pH 8.15. Following incubation at 37°c, the NEFA (non esterified fatty acids) produced were assayed hourly for 4 hours. LPL activity was expressed as µmol/l/min after subtraction of hepatic lipase (HL) activity, obtained following LPL inhibition with NaCl 1.5 mmol/l. Molecular analysis of LPL, GPIHBP1, APOA5, APOC2, APOE genes was available for 62 patients.Our method was reproducible (coefficient of variation (CV): intra-assay 5.6%, inter-assay 7.1%), and tightly correlated with the conventional radiolabelled triolein emulsion method (n = 26, r = 0.88). Normal values were established at 34.8 ± 12.8 µmol/l/min (mean ± SD) from 20 control subjects. LPL activities obtained from 71 patients with documented history of major hypertriglyceridemia showed a trimodal distribution. Among the 11 patients with a very low LPL activity (< 10 µmol/l/min), 5 were homozygous or compound heterozygous for LPL or GPIHBP1 deleterious mutations, 3 were compound heterozygous for APOA5 deleterious mutations and the p.S19W APOA5 susceptibility variant, and 2 were free of any mutations in the usual candidate genes. No homozygous gene alteration in LPL, GPIHBP1 and APOC2 genes was found in any of the patients with LPL activity > 10 µmol/l/min.This new reproducible method is a valuable tool for routine diagnosis and reliably identifies LPL activity defects.